Study on dynamic characteristics variation mechanism of wet-clutches during the filling phase considering temperature and rotational speed of the oil. (June 2023) - Ren, Yanfei; Xi, Junqiang; Chen, Huiyan; Yu, Huilong; Meng, Fei; Zhou, Wei
Abstract: A deep insight into the complex dynamic characteristics of wet-clutches can help to improve control accuracy of the filling phase in the clutch-to-clutch shift process of an automatic transmission (AT). Existing research focuses on ideal operating conditions, where the effects of oil temperature and its rotational speed are rarely considered. To deeply understand the variation mechanism of dynamic characteristics of the wet-clutch, this paper proposes an accurate model by accounting for oil temperature and rotational speed. In this model, the centrifugal force, elastic resistance, and axial friction are respectively included based on the theory of fluid dynamics. The effects of oil temperature on key parameters of the model are then described by using an exponential function. The comparison between the simulation and experimental results shows that the proposed model has a comparatively better performance compared to the experiment and conventional model. Based on the model, the influences of these factors on the dynamics of the wet-clutch during the filling phase are analyzed, and the influence laws are obtained. Highlights: A dynamic model is proposed for a wet-clutch considering oil temperature and its rotation. Three parameter variation laws with oil temperature are obtained and modeled. The proposed model is verified by comparison experiment and conventional model. Effects of temperature and its rotation on the dynamics of the wet-clutch are analyzed.